2011
DOI: 10.1007/s00415-011-6259-7
|View full text |Cite|
|
Sign up to set email alerts
|

CHA2DS2-VASc score and prognosis in ischemic strokes with atrial fibrillation

Abstract: The CHA(2)DS(2)-VASc score was developed to improve stroke risk stratification in atrial fibrillation (AF) patients. We sought to analyze the distribution and prognostic value of the CHA(2)DS(2)-VASc score in a cohort of ischemic stroke patients with AF. In total, 439 consecutive stroke patients with AF were studied. The CHA(2)DS(2)-VASc score was calculated according to clinical status before stroke onset. Poor outcome was defined as a modified Rankin score of 3 to 6 at 3 months. Association between CHA(2)DS(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…These risk stratification schemes may also be useful for predicting clinical outcomes in ischemic stroke or transient ischemic attack (TIA) patients with AF. In fact, we [4, 5] and others [6-9] have reported positive associations between pre-admission CHADS 2 and CHA 2 DS 2 -VASc scores and poor clinical outcomes in ischemic stroke patients with AF. In these studies, however, clinical outcomes were assessed at ≤3 months.…”
Section: Introductionmentioning
confidence: 99%
“…These risk stratification schemes may also be useful for predicting clinical outcomes in ischemic stroke or transient ischemic attack (TIA) patients with AF. In fact, we [4, 5] and others [6-9] have reported positive associations between pre-admission CHADS 2 and CHA 2 DS 2 -VASc scores and poor clinical outcomes in ischemic stroke patients with AF. In these studies, however, clinical outcomes were assessed at ≤3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Giralt-Steinhauer et al enrolled 439 stroke patients with AF and reported that a higher CHA2DS2-VASc score was associated with poor 3-month functional outcome (OR, 1.36; P=0.001). 26 In contrast, Tu et al found that low prestroke CHA2DS2-VASc score had high specificity for good functional outcome within 3 months following stroke in patients with or without AF. 27 …”
Section: Discussionmentioning
confidence: 93%
“…Whereas, several past studies were retrospective and used only a single assessment score [2][3][4][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective studies CHA2DS2-VASc score have been suggested as a predictor of severity of stroke at admission and poor outcome [2][3][4] .…”
Section: Background and Purposementioning
confidence: 99%